PENERAPAN PENDEKATAN TEACHING AT THE RIGHT LEVEL (TARL) UNTUK MENINGKATKAN HASIL BELAJAR BAHASA INDONESIA SISWA KELAS II-B SD NEGERI 25 PALU: Penelitian Tindakan Kelas - Armayanti; Nasrullah; Umira Rusagau (STKIP Subang, 2025)
This study is categorized as Classroom Action Research (CAR), systematically designed to examine and improve Indonesian language literacy through the application of Teaching at the Right Level (TaRL) as a differentiated instructional model. The research involved 24 second grade students at SD Negeri 25 Palu, consisting of 14 boys and 10 girls. Quantitative data were collected using standardized tests to assess conceptual understanding and the progression of learning outcomes over time. The analysis demonstrated a steady improvement during the pre action phase 14 students (58%) met mastery criteria, which increased to 18 students (75%) in cycle I and reached 20 students (83%) in cycle II. These findings confirm the effectiveness of TaRL as an adaptive instructional approach that aligns teaching strategies with the actual readiness levels of students, while accommodating diverse initial abilities. Therefore, TaRL stands out as a strategic and evidence-based innovation capable of significantly enhancing the quality of Indonesian language instruction at the elementary level.